Model-based condition monitoring of piezoelectric bending actuators - Bender, Amelie (Sensors and Actuators A: Physical)
With enhancing digitalization, condition monitoring is used in an increasing number of application fields across various industrial sectors. By its application, increased reliability as well as reduced risks and costs can be achieved. Based on different approaches, technical systems are monitored and measured data is analyzed to enable condition-based or predictive maintenance. To this end, machine learning approaches are usually implemented to diagnose the health states or predict the health index of the monitored system. However, these trained models are often black-box models, not intuitively explainable for a human. To overcome this shortcoming, a model-based approach based on physics is developed for piezoelectric bending actuators. Such a model enables a transparent representation of the system. Moreover, the model-based approach is extended by a parameter-estimation to account for sudden changes in behavior e. g. caused by occurring cracks.
Keywords: Condition Monitoring; Model-based approach Diagnostics; Varying conditions; Explainability; Piezoelectric bending actuators

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

Anregungskonzepte und Modellierung piezoelektrischer Trägheitsmotoren - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (7. Paderborner Workshop Entwurf mechatronischer Systeme)
Piezoelektrische Trägheitsmotoren nutzen die Trägheit einer bewegten Masse, um diese in kleinen Schritten durch abwechselnde Haft- und Gleitphasen voranzutreiben. Eine Kernfrage bei der Entwicklung eines piezoelektrischen Trägheitsmotors ist, welches elektrische Ansteuersignal für das gewünschte Motorverhalten optimal ist. Das elektrische Signal führt zu einer Bewegung des piezoelektrischen Aktors und damit der Antriebsstange, die den reibschlüssigen Vortrieb bewirkt. Entsprechend wird diese Fragestellung in zwei Teilen untersucht: Anhand eines Starrkörpermodells werden zunächst Bewegungsverläufe für die Antriebsstange ermittelt, mit denen die maximale Geschwindigkeit erreicht wird. Dabei werden drei Antriebsmodi identifiziert. Mit allen kann eine höhere Geschwindigkeit als mit der heute häufig verwendeten Sägezahnanregung erreicht werden. Anschließend wird ein einfaches dynamisches Modell eines piezoelektrischen Aktors genutzt, um die notwendigen elektrischen Ansteuersignale für die verschiedenen Antriebsmodi zu bestimmen. Es zeigt sich, dass das gewählte einfache Modell hierzu nur bedingt geeignet ist.
Keywords: Piezoelektrischer Trägheitsmotoren

Improving the Performance of Piezoelectric Inertia Motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2010 Conference Proceedings)
A model based design approach for improved piezoelectric inertia motors is presented. Three velocityoptimized movement patterns for the driving body have been derived. The influence of the motor parameters and the process of designing an application specific motor with maximum velocity are shown. A simple dynamic model of the piezoelectric actuator is used to calculate the voltage signal for achieving the desired movement pattern. Observed distortions of the optimum pattern, their influence on the motion of the driven body and different methods to reduce them are discussed.

Electro-thermo-mechanical analytical modeling of multilayer cantilever microactuator - Jiang, Jianliang; Hilleringmann, Ulrich; Shui, Xiaoping (Sensors and Actuators A: Physical)
Keywords: Electrical and Electronic Engineering; Metals and Alloys; Surfaces; Coatings and Films; Condensed Matter Physics; Instrumentation; Electronic; Optical and Magnetic Materials

Ultrasonic density sensor - analysis of errors due to thin layers of deposits on the sensor surface - Püttmer, A; Hoppe, N; Henning, Bernd; Hauptmann, P (Sensors and Actuators A: Physical)

Improved ultrasonic density sensor with reduced diffraction influence - Püttmer, A.; Lucklum, R.; Henning, Bernd; Hauptmann, P. (Sensors and Actuators A: Physical)

A low-voltage torsional actuator for application in RF-microswitches - Plotz, R; Michaelis, S; Aigner, R; Timme, HJ; Binder, J; Noé, Reinhold (SENSORS AND ACTUATORS A-PHYSICAL)

A low-voltage torsional actuator for application in RF-microswitches - Plotz, R; Michaelis, S; Aigner, R; Timme, HJ; Binder, J; Noé, Reinhold (SENSORS AND ACTUATORS A-PHYSICAL)